Application of Solid Long-lived Radon Progeny210Po in the Location Detection of Coal Spontaneous Combustion in Goaf - Chen LIN; Junfeng WANG; Kaili Dong; Xuan LIU (Taiyuan Ligong Daxue xuebao, 2023)
Aiming at the shortcomings of isotope radon detection method, which has large workload, long period, and is easily restricted by climate and environmental factors this paper proposes the use of radon generated during the process of migration to the surface to accurately reflects the solid-state length of the cumulative value of parent radon over a period of time. Long-lived radon daughter 210Po fire detection method based on radiochemical analysis method to measure 210Po activity concentration to detect hidden mine fire areas. In order to explore the effect and accuracy of the radon progeny 210Po fire detection method in on-site detection, this paper carried out on-site experimental research in Liuwan Coal Mine where the fire source location is known. The radon gas concentration at the measuring point and the activity concentration of its solid long-lived daughter 210Po are measured. By comparing the correlation between radon gas concentration and 210Po activity concentration detection results and its influencing factors, the technology of using radon daughter 210Po to detect the location of coal spontaneous combustion in goaf is demonstrated. The results show that the radon concentration in the near-surface soil layer in the fire area has a strong correlation with the 210Po activity concentration in the overall distribution, but the 210Po activity concentration is less disturbed by external factors, and its distribution can more accurately reflect the underground coal spontaneous combustion fire area. Compared with the isotope radon detection method, the radon progeny 210Po fire detection method has higher detection accuracy, wider application range and higher application value.